2019
DOI: 10.1097/ta.0000000000002372
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of scores and predictors to trigger activation of massive transfusion protocols

Abstract: BACKGROUND The use of massive transfusion protocols (MTPs) in the resuscitation of hemorrhaging trauma patients ensures rapid delivery of blood products to improve outcomes, where the decision to trigger MTPs early is important. Scores and tools to predict the need for MTP activation have been developed for use to aid with clinical judgment. We performed a systematic review to assess (1) the scores and tools available to predict MTP in trauma patients, (2) their clinical value and diagnostic accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…For children, no such tool exists that takes into account the differences in physiology and common injury patterns that predominate in pediatric trauma. 26 However, the ideal pediatric MT prognostic tool would capture prehospital or admission hemodynamic variables, be simple, and would integrate automatically within the workflow of the resuscitation team. At present, the only validated scoring systems for children relay mortality prediction capabilities rather than signaling the need for MT.…”
Section: Triggers For Massive Transfusion and Predictors Of Massive Transfusionmentioning
confidence: 99%
“…For children, no such tool exists that takes into account the differences in physiology and common injury patterns that predominate in pediatric trauma. 26 However, the ideal pediatric MT prognostic tool would capture prehospital or admission hemodynamic variables, be simple, and would integrate automatically within the workflow of the resuscitation team. At present, the only validated scoring systems for children relay mortality prediction capabilities rather than signaling the need for MT.…”
Section: Triggers For Massive Transfusion and Predictors Of Massive Transfusionmentioning
confidence: 99%
“…This randomized method is also feasible, as we have collected data from 60 cases using this approach. Another problem is that patients in the SICU tend to need massive transfusion, and consequently, such need will increase the difficulty in using the framed age donor’s blood [ 24 , 25 ]. If a patient requires a massive transfusion while the framed age donor’s blood is not available, we will have to exclude this case from the DAIP investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The TASH score is based on a logistic function of several clinical markers (sex, hemoglobin, base excess, systolic blood pressure, heart rate, injuries, or findings suspected of bleeding). From the various existing scores predicting massive transfusion after multiple injuries, we chose the TASH score because this score is well validated, and its overall accuracy seems to be superior to others [ 16 , 36 , 37 ]. Indeed, of all the scores in our study the TASH score showed the best, although only fair, correlation with the number of PRBC and FFP transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides anatomical injury scores like the well-known Injury Severity Score (ISS), which itself is based on the so-called Abbreviated Injury Scale (AIS), there are also a number of physiological and combined scoring systems [ 15 ]. In a recent systematic review, Shih et al assessed clinical scores and tools to predict the need for activation of a massive transfusion protocol [ 16 ]. Nevertheless, to the best of our knowledge, the capability of trauma scores to directly predict changes of clotting factor activities following severe trauma has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%